Guide pour les utilisateurs de la tablette et de la plateforme Formation À Distance - Ranaivosamoelina, Tokiniaina; Rasolohery, Hasiniavo (EdTech Hub, 2025)
This is a practical guide for users of a tablet for the distance learning platform (FAD), specifically for 2000 primary teachers in Madagascar. It covers: Tablet Basics: How to use the tablet, buttons, screen, touch controls, navigation, and settings. Accessories: Information on the solar charger / power bank and mini-speaker. Communication: Instructions on making calls, sending SMS and emails, and accessing the internet. Applications: Guides for using applications for training content and exercises. Online Platform: Instructions for accessing and using the Moodle online platform for assessments and resources. Tablet Care: Tips for protecting the tablet and optimizing battery life. The guide is intended for beginners and provides step-by-step instructions with illustrations. It also includes a list of abbreviations and acronyms. Keywords: teacher professional development; Madagascar; Moodle; tablet; user guide Ceci est un guide pratique destiné aux utilisateurs d’une tablette pour la plateforme d’apprentissage à distance (FAD), spécifiquement conçu pour 2000 enseignants du primaire à Madagascar. Il couvre : Bases de la tablette : Utilisation de la tablette, boutons, écran, commandes tactiles, navigation et paramètres. Accessoires : Informations sur le chargeur solaire/batterie externe et le mini-haut-parleur. Communication : Instructions pour passer des appels, envoyer des SMS et des e-mails, et accéder à Internet. Applications : Guides d’utilisation des applications pour les contenus de formation et les exercices. Plateforme en ligne : Instructions pour accéder et utiliser la plateforme Moodle pour les évaluations et les ressources. Entretien de la tablette : Conseils pour protéger la tablette et optimiser l’autonomie de la batterie. Ce guide est destiné aux débutants et propose des instructions pas à pas avec illustrations. Il comprend également une liste d’abréviations et d’acronymes. Mots clés: formation pédagogique; Madagascar; Moodle; tablette; guide pour les utilisateurs An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14230784 ZenodoArchiveConcept: 14230783 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1066 10.53832/edtechhub.1073
Keywords: _r:AddedByMyEducationEvidence

Guide pour les administrateurs de la plateforme Formation À Distance - Rasolohery, Hasiniavo; Ranaivosamoelina, Tokiniaina (EdTech Hub, 2025)
This is a practical guide for administrators of the Formation À Distance (FAD) platform in Madagascar. The guide provides instructions on managing the platform, with a focus on evaluations and forums. It covers topics such as setting up different types of evaluations (quizzes, assignments), configuring forum settings, managing discussions, and moderating forums. It also includes best practices for both evaluations and forums, as well as security considerations. The document provides step-by-step instructions with screenshots for specific tasks like activating edit mode, adding activities or resources, setting up tests, and configuring forum parameters. It also includes a glossary of terms, references, and useful links. The guide is intended to help administrators effectively manage the FAD platform and support teachers and students in their online learning activities. Keywords: teacher professional development; Madagascar; Moodle; tablet; administrator guide Ceci est un guide pratique destiné aux administrateurs de la plateforme de Formation À Distance (FAD) à Madagascar. Il fournit des instructions pour la gestion de la plateforme, en mettant l’accent sur les évaluations et les forums. Il couvre des sujets tels que la configuration des différents types d’évaluations (quiz, devoirs), le paramétrage des forums, la gestion des discussions et la modération des forums. Il inclut également les meilleures pratiques pour les évaluations et les forums, ainsi que des considérations de sécurité. Le document propose des instructions détaillées, illustrées par des captures d’écran, pour des tâches spécifiques comme l’activation du mode édition, l’ajout d’activités ou de ressources, la mise en place de tests et le paramétrage des forums. Il comprend également un glossaire des termes, des références et des liens utiles. Ce guide vise à aider les administrateurs à gérer efficacement la plateforme FAD et à soutenir les enseignants et les élèves dans leurs activités d’apprentissage en ligne. Mots clés: formation pédagogique; Madagascar; Moodle; tablette; guide pour les administrateurs An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14230806 ZenodoArchiveConcept: 14230805 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1062 10.53832/edtechhub.1074
Keywords: _r:AddedByMyEducationEvidence

Minoritised Languages, Education, and Technology: Current practices and future directions in low- and middle-income countries - Zhao, Annette; Mitchell, Joel; Gasanabandi, Gentille; Ullah, Noor; Barnes, Katrina; Koomar, Saalim (EdTech Hub, 2024)
This article explores the current status and future directions of mother-tongue-based multilingual education (MTB MLE) and the use of technology in low- and middle-income countries (LMICs), focusing on the use of minoritised mother tongues. An initial literature review of available academic sources in multiple languages reveals a lack of evidence on the use of technology in MTB MLE across different countries, especially multilingual contexts with greater linguistic diversity. To understand the issue in greater detail and to offer recommendations informed by current practice, interviews and a collaborative workshop with four organisations with relevant educational technology (EdTech) initiatives were conducted. The analysis covers facilitating and limiting factors these organisations have encountered, and the potential positive impact on learners and society generally. We conclude by identifying practical, policy, and research priorities for multilingual education and educational technology in general.
ZenodoArchiveID: 7267302 ZenodoArchiveConcept: 7267301 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7267302 10.53832/edtechhub.0127 2339240:V7ARHU93 2405685:GBBGHCBH 2405685:QADQUWU3 2405685:UTTZNZ24
Keywords: _r:AddedByZotZen